Improving access to suicide prevention services through the National Suicide Prevention Framework implementation: The community level evidence-based recommendations - J C Y Nyasulu; D A Siddiqi; S Seedat; J Bantjies; M Udedi; S Gondwe; S Kambale; M Mkandawire; N Silungwe; L A Hendricks; I Maposa; J Vumu; et al. (South African Medical Journal)
-